Recurrent genital herpes: clinical and virological features in men and women. Issue 2 (April 1988) - Mindel, A; Coker, D M; Faherty, A; Williams, P
Abstract : One hundred and forty eight patients (69 women and 79 men) with often recurring genital herpes were observed for two months. Men had 119 observed recurrences and women 104. The attacks were significantly longer in men than women (8.7 days v 6.6 days, p = 0.005). Significantly more women complained of symptoms, however, and when symptoms occurred they were more severe. Other significant differences between men and women included age (men were older than women); more men had previously had sexually transmitted diseases; more men had infected a sexual partner, but fewer knew the source of their infection; and men had more lesions at each attack. Positive viral culture results were shown to depend on the amount of erythema, the number of lesions, and the presence of vesicles.